Optimization of low-density polyethylene (LDPE) in eco-paving block synthesis: A pathway toward community empowerment - Fasdarsyah Fasdarsyah; Herman Fithra; Nura Usrina; Nanda Savira Ersa; Zara Yunizar; Muhammad Fauzan; Zulnazri; Febi Anriani; Maulida Yani Siregar (LPPM Universitas Syiah Kuala, 2026)
Background and Aim: Blang Asan Village has economic potential in the brick production sector; however, production activities are still conventional and have not integrated innovations in construction material technology. In addition, unmanaged Low-Density Polyethylene (LDPE) plastic waste contributes to environmental problems. This community service activity aimed to implement a circular economy concept by transforming LDPE plastic waste into environmentally friendly construction materials in the form of eco-paving blocks. Methods: The program was implemented using an experimental and participatory approach involving local partners through socialization, technical training, and construction implementation assistance. Laboratory testing was conducted on six specimen variations molded using 3 kg hexagonal molds. The mixtures consisted of LDPE plastic waste, fine aggregate, coarse aggregate, cement, and varying amounts of used oil. Compressive strength tests were performed to determine the optimal composition. Results: The compressive strength test showed that the best composition was obtained with 15% LDPE without an oil mixture, producing a compressive strength value of 24.2 MPa. Based on SNI 03-0691-1996 standards, the product met the B Quality criteria, making it suitable for parking area applications. The program successfully transferred technology to local brick craftsmen, enabling them to independently produce eco-friendly construction materials. Conclusion: The application of LDPE-based eco-paving blocks effectively reduced plastic waste while creating value-added construction products with economic potential. This program also supported the development of sustainable green economy practices in Blang Asan Village.